PAX7, PAX9 and RYK Expression in Cleft Affected Tissue - Mārtiņš Vaivads; Ilze Akota; Māra Pilmane (Medicina, 2021)
Background and Objectives: Cleft lip with or without cleft palate is one of the most common types of congenital malformations. Transcription factors paired box 7 and 9 (PAX7, PAX9) and receptor-like tyrosine kinase (RYK) have been previously associated with the formation of orofacial clefts but their exact possible involvement and interactions in the tissue of specific cleft types remains uncertain. There is a limited number of morphological studies analyzing these specific factors in cleft affected tissue due to ethical aspects and the limited amount of available tissue material. This study analyses the presence of PAX7, PAX9, and RYK immunopositive structures within different cleft affected tissue to assess their possible involvement in cleft morphopathogenesis. Materials and Methods: Cleft affected tissue was collected from non-syndromic orofacial cleft patients during cleft correcting surgery (36 patients with unilateral cleft lip, 13 patients with bilateral cleft lip, 26 patients with isolated cleft palate). Control group oral cavity tissue was obtained from 7 patients without cleft lip and palate. To evaluate the number of immunopositive structures in the cleft affected tissue and the control group, a semiquantitative counting method was used. Non-parametric statistical methods (Kruskal–Wallis H test, Mann–Whitney U test, and Spearman’s rank correlation) were used. Results: Statistically significant differences for the number of PAX7, PAX9, and RYK-positive cells were notified between the controls and the patient groups. Multiple statistically significant correlations between the factors were found in each cleft affected tissue group. Conclusions: PAX7, PAX9, and RYK have a variable involvement and interaction in postnatal morphopathogenesis of orofacial clefts. PAX7 is more associated with the formation of unilateral cleft lip, while PAX9 relates more towards the isolated cleft palate. The stable presence of RYK in all cleft types indicates its possible participation in different facial cleft formations.